2022
DOI: 10.1080/21655979.2022.2051853
|View full text |Cite
|
Sign up to set email alerts
|

RAB26 contributes to the progression of non-small cell lung cancer after being transcriptionally activated by SMAD3

Abstract: Non-small cell lung cancer (NSCLC) accounts for 85% of all cases of lung cancer, which constitutes the leading cause of cancer mortality. RAB26, a member of Rab GTPase superfamily, has been suggested to play a role in the tumorigenesis of NSCLC. The present work aimed to explore whether and how RAB26 contributed to the progression of NSCLC. NSCLC cell line A549 was transfection with short hairpin RNA (shRNA) or overexpression (Ov) vector to knockdown RAB26 or overexpress SMAD3, respectively. Then the malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…32 Rab26 has been implicated in NSCLC progression in previous studies. 16,17 Importantly, our study showed that silencing Rab26 only slightly suppressed the proliferation of cisplatin-resistant A549/DDP lung cancer cells, but silencing Rab26 could partially reverse the cisplatin drug resistance of A549/DDP, suggesting that Rab26 is an essential regulator in the cisplatin resistance of A549/DDP. The regulation of cell autophagy (including mitophagy) can be an effective strategy to control resistance in lung cancer.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…32 Rab26 has been implicated in NSCLC progression in previous studies. 16,17 Importantly, our study showed that silencing Rab26 only slightly suppressed the proliferation of cisplatin-resistant A549/DDP lung cancer cells, but silencing Rab26 could partially reverse the cisplatin drug resistance of A549/DDP, suggesting that Rab26 is an essential regulator in the cisplatin resistance of A549/DDP. The regulation of cell autophagy (including mitophagy) can be an effective strategy to control resistance in lung cancer.…”
Section: Discussionmentioning
confidence: 72%
“…Rab26 has also been implicated in lysosome trafficking, mitochondrial redistribution, and autophagy induction in neuronal somata. , Rab26 is already known to be involved in lung cancer. Its expression gradually increased from stage I to VI in NSCLC tissues compared with normal tissues . Additionally, Rab26 supplementation partially restored oncogenicity, whereas it was inhibited in normal lung cancer cells .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The cell lysates were incubated with anti-SP1 (ab231778, 1:100, Abcam Inc., Cambridge, MA, USA) or normal rabbit antibody immunoglobulin G (IgG, ab172730, 1:100, Abcam) at 4°C overnight. The DNA was diluted using ChIP dilution buffer, and the abundance of SP1 was examined by qPCR [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…In line with this observation, a recent study showed that Rab3c promotes cell migration and correlates with poor prognosis in colon cancer by regulating the ability of cancer cells to release IL-6 via exocytosis and activating the JAK2-STAT3 pathway [56]. In addition, S-SMAD3, a key modulator in the TGF-β mediated transcriptional activation that drives epithelial-mesenchymal transition (EMT) and cell migration, binds to the promoter of Rab26 gene, thereby increasing its expression to enhance cancer progression [57]. This is suggestive of the Rab proteins' role in oncogenic signaling to direct tumor progression.…”
Section: Cooperating Rab-mediated Tumorigenesis With Cancer Cell Sign...mentioning
confidence: 99%